Sport and Physical Activity across the Lifespan Critical Perspectives (Palgrave Macmillan UK, 2018)
This edited collection problematizes trajectories of health promotion across the lifespan. It provides a distinctive critical social science perspective of the various directions taken by dominant policies in their approach to promoting sport for all ages. It offers an array of theoretical and methodologically diverse perspectives on this topic, and highlights the intersections between different life stages and social, economic and cultural factors in the developed world, including class, gender, ability, family dynamics and/or race. Sport and Physical Activity across the Lifespan critically explores dominant policies of age-focussed sport promotion in order to highlight its implications within the context of particular life stages as they intersect with social, cultural and economic factors. This includes an examination of organised sport for pre-schoolers; 'at-risk' youth sport programmes; and the creation of sporting sub-cultures within the mid-life 'market'. This book will be of interest to those wanting to learning more about how age and life stages affect the way people think about and participate in sport, and to better understand the impacts of sport across the lifespan.